2015
DOI: 10.1105/tpc.114.131508
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Dissociation of the BSS1 Protein Complex Regulates Plant Development via Brassinosteroid Signaling

Abstract: JapanBrassinosteroids (BRs) play important roles in plant development and the response to environmental cues. BIL1/BZR1 is a master transcription factor in BR signaling, but the mechanisms that lead to the finely tuned targeting of BIL1/BZR1 by BRs are unknown. Here, we identified BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) as a negative regulator of BR signaling in a chemical-biological analysis involving brassinazole (Brz), a specific BR biosynthesis inhibitor. The bss1-1D mutant, which overexpresses BSS1, exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…5c). A similar punctate BiFC signal has been previously reported for BZR1 with BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) 50 or BES1 with DOMINANT SUPPRESSOR OF KAR 2 (DSK2) 7 , although its significance remains unknown.…”
Section: Resultssupporting
confidence: 80%
“…5c). A similar punctate BiFC signal has been previously reported for BZR1 with BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) 50 or BES1 with DOMINANT SUPPRESSOR OF KAR 2 (DSK2) 7 , although its significance remains unknown.…”
Section: Resultssupporting
confidence: 80%
“…BIN2-induced phosphorylation inactivates BES1 and BZR1 by promoting their cytoplasmic retention via 14-3-3 proteins (Gampala et al, 2007;Ryu et al, 2007), inhibiting their DNA binding activity (Vert and Chory, 2006), and stimulating their degradation Yin et al, 2002;Nolan et al, 2017b;Kim et al, 2019). Moreover, BES1 and BZR1 are kept in an inactivate state through interactions with the BROAD COMPLEX/TRAMTRACK/BRIC-A-BRAC family protein BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) under BR-deficient conditions (Shimada et al, 2015).…”
Section: Inhibition Of Br Signalingmentioning
confidence: 99%
“…BSS1, also known as BLADE ON PETIOLE1 (BOP1), acts as part of a CUL3 BOP1/BOP2 E3 ubiquitin ligase complex that facilitates PIF4 degradation during photomorphogenesis . Thus, given that BSS1/BOP1 also interacts with BES1 and BZR1 and affects their protein levels (Shimada et al, 2015), it would be interesting to determine if BSS1 plays a role in BES1 and BZR1 ubiquitination.…”
Section: Bes1 and Bzr1 Regulation: More Than Just Phosphorylationmentioning
confidence: 99%
“…At the BIN2 level, it has been reported that BIN2 is regulated by OCTOPUSor POLAR-mediated membrane sequestration, HDA6-mediated deacetylation, KIB1-mediated ubiquitination, TTL-enhanced interaction with BSU1, ABI1/2-mediated dephosphorylation, and ROS (reactive oxygen species)-mediated oxidation [74][75][76][77][78][79][80]. At the transcription level, it has been reported that PP2A phosphatases can promote BR signaling by dephosphorylating BES1 and BZR1, whereas 14-3-3 and BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) negatively regulate BR signaling by inhibiting the translocation of BES1 and BZR1 from the cytosol to the nucleus [81][82][83]. Besides, protein degradation of BES1 and/or BZR1 has been reported to be regulated by many factors, including an F-box protein MORE AXILLARY GROWTH LOCUS2 (MAX2), ubiquitin E3 ligases such as PLANT U-BOX40 (PUB40), CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) and SINA of Arabidopsis thaliana (SINATs), photoreceptors such as UV RESISTANCE LOCUS 8 (UVR8), CRYPTOCHROME1 (CRY1) and PHYTOCHROME B (PHYB), and an autophagy receptor DOMINANT SUPPRESSOR OF KAR2 (DSK2) [84][85][86][87][88][89][90][91][92][93].…”
mentioning
confidence: 99%